Chemistry for the Protection of the Environment 4 - Mournighan, Robert; Dudzinska, Marzenna R.; Barich, John.; Gonzalez, Marjorie A.; Black, Robin K.; SpringerLink (Online service) (New York, NY : Springer US : Imprint: Springer, 2005)
Chemistry for the Protection of the Environment 4 focuses on: • Environmental aspects of agricultural practices • Field characterization and quantification of chemical constituents • Fate of contaminants in the environment/environmental monitoring • Thermal treatment technologies • Remediation of contaminated sites • Wastewater treatment and sludge management • Environmental Security • Risk Assessment and Environmental Management This volume is the proceedings of the first CPE conference in the new millennium and the thirteenth in a well-established series of conferences on Chemistry for the Protection of the Environment, first established in 1976. With support of the U.S. EPA, the series of conferences provides an opportunity for interdisciplinary exchange of ideas among international specialists, from diverse fields and backgrounds, on the chemical aspects of environmental protection. Over the years, the CPE conferences have gathered participants from more and more countries, and the scope of interests have been broadened. Held in Hilo, Hawaii, this was the first of these international conferences to take place in the United States. The Organizing Committee attracted to the conference a wide range of talented scientists and engineers who have useful ideas to contribute on how to clean our environment. Any pollution control or pollution cure action today must take into consideration not only one element of the environment, like water, air or soil but also proper environmental handling and related problems. In all cases, chemical processes play a highly significant role. In recent years there has been a shift from wastewater technologies and pollutant monitoring problems to environment management and solid wastes issues. This book provides a forum for chemical scientists and engineers who are dedicated to the worthy mission of making a cleaner, healthier world for everyone. The central goals of Chemistry for the Protection of the Environment are to improve technology transfer and scientific dialogue, thereby leading to better comprehension of and solution to a broad spectrum of environmentally related problems.
Remediation of Contaminated Sites -- Study of the Clinoptilolite-Rich Tuff-Based Composites for Some Aqueous Anionic Species Recovery -- Testing of Sorption Materials for Arsenic Removal From Waters -- Zirconium(IV) Loaded Diaion CRP200 Resin as a Specific Adsorbent to as(III) and as(V) -- Bifunctional Cation Exchange Fibers Having Phosphonic and Sulfonic Acid Groups -- Fate of Contaminants in the Environment -- Arsenic Speciation for Investigation of Its Environmental Fate — A Case Study -- Chemical Speciation of Aluminum in Delhi Soils -- Thermal Treatment Technologies -- Thermal and Biological Degradation of Sites Contaminated by Transformer Oil -- Plasma Treatment of Inorganic Waste -- Environmental Aspects of Agricultural Practices -- Former U.S. Department of Agriculture/Commodity Credit Corporation Grain Bin Project -- Agricultural Biotechnology: Public Acceptance, Regulation and International Consensus -- Charactization and Quantification of Chemical Constituents -- Rapid On-Site Environmental Sampling and Analysis of Propellant Stabilizers and Their Decomposition Products by Portable Sampling and Thin-Layer Chromatography Kits -- Comparative Multi-Elemental Analysis of Mineral and Ecological Components of the Ecosystem “Karabashtown” Co-Existing with a Copper-Smelting Plant. Physicochemical Point of View -- Automated Analysis of Stable Isotopes of H, C, N, O and S by Isotope Ratio Mass Spectrometry -- Environmental Security -- Relationship of Environment and Security -- Integrated Risk Assessment and Security -- Risk Assessment -- Hazard Assessment of Maalaea Construction and Demolition Landfill Smoldering Fire, and Air Quality at a Nearby Community -- Methods for Estimating the Impact of Hypothetical Dam Break Floods -- Wastewater and Sludge Management -- Polychlorinated Dibenzo-P-Dioxins (PCDDs) and Dibenzofurans (PCDFs) in Sewage and Sludge of MWTP -- The Utilization of Sludge Generated in Coagulation of Fish Processing Wastewater for Liquid Feed Production -- Sustainable Development in Industry by Closing Water Loops:Technological Aspects and Expected Future Developments -- Optimisation of Reactor Technology for Selective Oxidation of Toxic Organic Pollutants in Wastewater by Ozone -- Comparison between Sequencing Batch and Continuous Flow Activated Sludge Systems.
Keywords: Chemistry; Environment; Waste management; Water pollution; Chemistry/Food Science, general; Environment, general; Waste Management/Waste Technology; Waste Water Technology / Water Pollution Control / Water Management / Aquatic Pollution